Studies on language friction in producing English utterances: Systematic literature review - Setiawan, Slamet; Suhartono, Suhartono; Nashruddin, Nashruddin; Susanto, Djoko; Ahmadi, Anas; Al-Obaydi, Liqaa Habeb; Ammade, Salasiah (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2025)
Speech errors can occur due to language activation and competition in the human brain as a symptom of language friction. Many researchers have studied the language friction and published their findings, indicating that the study about this issue is interesting to conduct. The current literature study aims to review previous research on language friction in terms of methods and linguistics theories applied in those studies. A systematic method was used in this research to select research articles on the language friction, and resulted in 17 articles to be reviewed. Those articles are published in Scopus indexed journals. It is found that in the last seven years, studies on language friction have shown an increasing trend, indicating that this issue is still relevant to study. In addition, most of them indicate that language friction has been analyzed based on psycholinguistics and sociolinguistics theories. However, it is not enough to study language friction from psycholinguistic and sociolinguistic perspectives, but also needs to be studied from ethnosociolinguistic perspective. This literature study can help educators and English language learners to choose learning methods by considering the language friction experienced by learners. Furthermore, by understanding the language friction, speech participants can overcome misunderstandings in communication.